Comparative Analysis of Financial Performance at PT. XL Axiata Tbk and PT. Telkom Indonesia Tbk Listed on the Indonesia Stock Exchange - Nurkhaeriah Amir; Abdi Akbar; Anwar Ramli; Hety Budiyanti; Nurman Nurman (International Journal of Economics, Management and Accounting (IJEMA), 2023)
This study aims to find out how to compare the financial performance of PT Telkom Indonesia Tbk and PT XL Axiata Tbk for the 2017-2022 period. The parameters used to compare the company's financial performance are by using financial ratios, namely Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio, Fixed Assets Turnover, Total Asset Turnover Net Profit Margin, Return on Assets and Return on Equity . The research data was obtained from PT Telkom Indonesia Tbk and PT XL Axiata Tbk company data which are listed on the Indonesia Stock Exchange (IDX). The research sample consists of data on the financial statements of the companies PT Telkom Indonesia Tbk and PT XL Axiata Tbk which are listed on the Indonesia Stock Exchange for 6 years, namely the period 2017-2022. The data analysis techniques used in this study are financial ratio analysis and the two-mean difference test. -average (independent sample t-test). Based on the results of the ratio analysis, it was found that the financial performance of PT. Telkom Indonesia Tbk which is good based on industry standards in terms of Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio, Total Assets Turnover, while for the financial performance of PT. XL Axiata Tbk which is good according to industry standards only in terms of Fixed Assets Turnover. The results of the Two-Average Difference Test (Independent Sample t-test) obtained that Current Ratio, Quick Ratio, Debt to Assets Ratio, Debt to Equity Ratio, Fixed Assets Turnover, Total Asset Turnover Net Profit Margin.